MANFAAT LIDAH BUAYA SEBAGAI MASKER UNTUK PERAWATAN KULIT TANGAN KERING - Murnalis Murnalis (JURNAL PENDIDIKAN DAN KELUARGA, 2019)
Abstract The purpose of this study was to analyze the effect of the use of Aloe Vera to overcome dry hand with different frequency of use. This research is an experimental study, the method used is quasi-experimental, the number of samples is 9 people each of three people for each group. Control group (X1) without the use of aloe vera, experimental group 1 (X2) with a frequency of 1 x three days, and experimental group 2 (X3) with a frequency of 1 x 7 days. Data analysis using Analysis of Variance (ANOVA), followed by Duncan test if there are significant differences in the results of analysis of variance. The results showed that 1) There was no change in the level of dry skin moisture in the control group 2) There was a change in the skin moisture level of the experimental treatment group 1 (X2) with the use of Aloe Vera 1 time 3 days, 3) A change in the moisture level of the hand skin dry in the experimental treatment group 2 (X3) with the use of Aloe Vera 1 time 7 days, 4) There were differences in the effect of dry hand care using Aloe Vera with three different treatments and treatment groups with a frequency of 1 time in 3 days had the best results.